The millenium report - Cordovez, Diego (2016)
In this article, the author analyzes the Millenium Report in which Kofi Annan defines new responsibilities for the United Nations, suggests changes that should be made in its structure and organization, and advances a new set of principles, concepts and ideas for international cooperation. For the author, one of the key ideas of this Report is change in the notion of collective security toward the enhancement of individual well being, human Rights and Human and sustainable development.